2019
DOI: 10.1002/jbm.a.36716
|View full text |Cite
|
Sign up to set email alerts
|

In situ syntheses of hydroxyapatite‐grafted graphene oxide composites

Abstract: In this study, we examined three different syntheses of hydroxyapatite (HAp) and graphene oxide–hydroxyapatite (GO–HAp) composites with a GO content of 9, 33, and 43% wt. The materials were prepared from various precursors of calcium and phosphate ions, using an in situ synthesis method, with mild conditions to avoid reducing the GO. In situ bonding technology proposed that calcium ions bond with GO at first and then HAp nanoflakes in situ grow on GO sheets, forming GO–HAp nanocomposite. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The absorption peaks at about 1423, 1225, and 1060 cm –1 are assigned to −OH from carboxyl, C–O–C from epoxy or ether and C–O from alkoxy, respectively. These results are in agreement with the literature …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The absorption peaks at about 1423, 1225, and 1060 cm –1 are assigned to −OH from carboxyl, C–O–C from epoxy or ether and C–O from alkoxy, respectively. These results are in agreement with the literature …”
Section: Resultssupporting
confidence: 94%
“…Graphene oxide was synthesized using a modified Hummers method. , Graphite (5 g) and sodium nitrate (3.8 g) were placed in a beaker in a salt/ice bath. Subsequently, 375 mL of concentrated sulfuric acid was added.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have demonstrated that the abundant mineralization related groups (epoxide, and carboxylic groups) on GO surface can act as effective nucleation sites for precipitating Ca 2+ , and then regulate the nucleation and growth process of HAP nanocrystals [21] , [22] . The HAP nanocrystals can form tight interfacial bonding with GO nanosheets and distribute homogeneously on the surface of GO nanosheets thus avoiding their aggregation [23] , [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a lot of synthesis routes have been developed, starting both from chemical, physical, and biological methods. Specifically, the most used iron oxide NPs synthesis methods, due to their relative simplicity and the ability to have a good control of the particles’ shape and size, include chemical precipitation, hydrothermal, sol–gel, electro-deposition, emulsion precipitation, surfactant mediated precipitation, microemulsion precipitation, and microwave assisted hydrothermal technique [ 9 , 10 , 11 , 12 , 13 , 14 ]. Therefore, the main synthesis techniques are generally based on chemical routes, which, as disadvantages, often require the necessity of high temperature/pressure and always need extra purification steps to remove organic substances and/or secondary products.…”
Section: Introductionmentioning
confidence: 99%